ANALISIS PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Perusahaan Kontruksi yang Terdaftar di BEI Tahun 2014-2017) - Listiyowati, Listiyowati; Indarti, Iin (LPPM Universitas Mataram, 2018)
This study aims to examine the effect of institutional ownership, independent commissioners on the value of the company with return on assets as intervening variables. The test results for a sample of 32 construction companies from 2014 to 2017 using path analysis. Institutional ownership and independent commissioners do not have a direct effect on company value and return on assets, while return on assets directly has a significant effect on the value of companies in construction companies on the IDX. While profitability is not able to mediate the effect of good corporate governance on firm value because of the Z Score under 1.98. For Square Multiple Correlation is 83.8% which indicates that the research capital framework is quite good at explaining the dependent variable.Keywords: Institutional Ownership, Independent Commissioner, Return On Assets, Company Valu